'On the slope of an erupting volcano': A qualitative study on the workplace violence experiences of psychiatric nurses - Ozturk, Gulhan Kucuk; Baser, Eylul; Engin, Esra (Wiley, 2024)
What is known on the subject?Workplace violence is common in healthcare.Workplace violence remains a complex and serious occupational hazard in healthcare.What this paper adds to existing knowledge?Since there is no study examining detailed explanations of experiences and perspectives of workplace violence among psychiatric nurses, this study will act as a guide for psychiatric nurses.This study provides information about how psychiatric nurses evaluate the concept of workplace violence from their perspective, what it means to them and the effects of workplace violence.What are the implications for practice?Considering the effects of workplace violence, a preventive, systematic and holistic approach should be used in psychiatry and community mental health centres.Supportive interventions should be used to improve the health and safety of psychiatric nurses and patients.IntroductionWorkplace violence is common in healthcare and remains a complex and serious occupational hazard.AimThis research was conducted to assess the workplace violence experiences and perspectives of psychiatric nurses.MethodThis study was a qualitative study conducted using a grounded theory approach method. The study was conducted between November 2022 and January 2023. The purposeful sampling method was used, and 11 psychiatric nurses were interviewed. Data were collected with an information form and a semi-structured interview form. The data were analysed using content analysis, and themes were created.FindingsThe ages of the psychiatric nurses ranged from 38 to 57 years. Themes and sub-themes related to the workplace violence experiences and perspectives of psychiatric nurses included the way of violence (rising tension, eruption of the volcano, unintentional violence and turning to ash) and empowerment (ash cloud and ring of fire).ConclusionPsychiatric nurses stated that they were exposed to verbal and physical violence for many reasons, that this situation seriously affected their physical, mental and social health and that in addition to the devastating effects of violence, they became stronger by developing various skills to protect against violence.Implications for PracticeSupportive interventions should be used to improve the health and safety of psychiatric nurses and patients. Strategies can be developed to include psychiatric nurses in occupational health nursing courses.
Keywords: experience; perspective; psychiatric nurse; qualitative study; workplace violence